Дослідження і розвиток експорту інформаційних послуг вітчизняних компаній до країн Східної Європи - Жила, Діана Олександрівна; Zhyla, Diana Oleksandrivna (Національний університет "Львівська політехніка", 2024)
Експортна діяльність є ключовою складовою економічної стратегії сучасного підприємства, що прагне до розвитку та зміцнення позицій на конкурентному ринку. Вихід на зовнішні ринки відкриває нові можливості для збільшення доходів, оптимізації виробничих витрат та покращення якості продукції. Залучення до міжнародної торгівлі дозволяє підприємству підвищити свою економічну стійкість, знизити ризики, пов'язані з коливаннями внутрішнього попиту, а також сприяє інтеграції у світову економіку. Експорт визначається як процес продажу та вивезення товарів або послуг за межі національної економіки для їх реалізації на зовнішніх ринках [1]. Об’єктом магістерської дипломної роботи є співробітництво України та Чеської Республіки у сфері науково-дослідної діяльності. Об’єктом дослідження на мікрорівні стало споживче товариство «Міські інформаційні системи». Основний напрям діяльності компанії – комп'ютерне програмування, але також вона займається електромонтажними роботами й надає послуги у сфері проводового електрозв'язку [2]. Об’єктом дослідження на макрорівні є Чеська Республіка. Предметом дипломної роботи є вдосконалення співробітництва між Україною та Чехією у сфері науково-дослідної діяльності компаній. Метою магістерською дипломної роботи є дослідження та аналіз співпраці України та країн Східної Європи у сфері спільної економічної діяльності підприємств. Поставленими завданнями були: - загальний огляд основної теоретичної та нормативної бази за предметом дослідження, яка включає наукову літературу, закони, міжнародні договори тощо; - загальний аналіз співробітництва України та Чеської Республіки на макроекономічному рівні у сфері експорту інформаційних та комп’ютерних послуг; - дослідження економічної діяльності підприємств України та Чеської Республіки на мікроекономічному рівні, на прикладі споживчого товариства «Міські інформаційні системи», зокрема загальному огляді його виробничо-господарської, міжнародно-економічної та науково-дослідної діяльності, що також передбачає розробку рекомендацій щодо удосконалення співробітництва України та Чехії; - вибір і деталізація заходів з удосконалення міжнародної економічної діяльності України та Чеської Республіки на прикладі експорту інформаційних технологій. Представлене у роботі споживче товариство "Міські інформаційні системи" здійснює експортну діяльність, орієнтуючись на європейський ринок, зокрема Чехію. Основними продуктами експорту є антивірусне програмне забезпечення, системи для автоматизації бізнесу, бухгалтерські програми, а також аутсорсингові послуги з технічної підтримки тощо [2]. З економічної точки зору, торгівля інформаційними послугами між Україною та Чеською Республікою демонструє стабільне зростання та високу потенційну вигоду для обох країн [3]. Однак порівняння основних економічних показників України та Чеської Республіки демонструє різні рівні економічного розвитку, торгівельної активності та інвестиційної привабливості [4]. Обсяг експорту інформаційних послуг до Чехії показував зростання з 2019 до 2021 року – з 235 тис. грн до 264 тис. грн, що свідчить про зростаючий попит на інформаційні послуги підприємства в Чехії [1]. Досліджуючи шляхи удосконалення експортної діяльності компанії було обрано та обгрунтовано двоетапний підхід [5]. Першим елементом є вдосконалення наявної організаційної структури, а саме скорочення кількості працівників поліграфії до однієї людини та передача відділу у підпорядкування до заступника директора з фінансових питань через збитковість відділу, оскільки створення окремого відділу міжнародної економічної діяльності тягне за собою додаткові витрати, то необхідно підвищити кваліфікацію вже наявних працівників економічного відділу шляхом додаткового навчання. Цей крок забезпечить кращу комунікацію між підприємством та його закордонними партнерами. Другим елементом для успішної інтеграції на чеський ринок компанії необхідно адаптувати свої продукти і сервіси, щоб вони відповідали вимогам місцевих споживачів, стандартам і законодавчим нормам. Це дозволить створити конкурентоспроможну пропозицію, яка відповідатиме культурним, мовним і технічним особливостям ринку. Результати виконаного аналізу можуть безпосередньо бути задіяні на практиці діяльності українських та закордонних підприємств для розвитку зовнішньоекономічних зв’язків України та країн Східної Європи, Чеської Республіки зокрема.

Export activities are a key component of the economic strategy of a modern enterprise seeking to develop and strengthen its position in a competitive market. Entering foreign markets opens up new opportunities for increasing revenues, optimising production costs and improving product quality. Involvement in international trade allows a company to increase its economic sustainability, reduce the risks associated with fluctuations in domestic demand, and facilitates integration into the global economy. Export is defined as the process of selling and exporting goods or services outside the national economy for sale in foreign markets [1]. The subject of the master's thesis is the cooperation between Ukraine and the Czech Republic in the field of research and development. The object of the study at the micro level is the consumer company Urban Information Systems. The main activity of the company is computer programming, but it also carries out electrical work and provides services in the field of wire telecommunications [2]. The object of research at the macro level is the Czech Republic. The subject of the thesis is the improvement of cooperation between Ukraine and the Czech Republic in the field of research and development activities of companies. The purpose of the master's thesis is to study and analyse the cooperation between Ukraine and Eastern European countries in the field of joint economic activity of enterprises. The objectives were as follows: - a general overview of the main theoretical and regulatory framework on the subject of the study, including scientific literature, laws, international treaties, etc; - a general analysis of cooperation between Ukraine and the Czech Republic at the macroeconomic level in the export of information and computer services; - study of economic activities of enterprises of Ukraine and the Czech Republic at the microeconomic level, on the example of the CC ‘Urban Information Systems’, including a general overview of its production and economic, international economic and research activities, which also involves the development of recommendations for improving cooperation between Ukraine and the Czech Republic; - selection and detailing of measures to improve the international economic activity of Ukraine and the Czech Republic on the example of information technology exports. The consumer company ‘Urban Information Systems’ presented in this paper carries out export activities, focusing on the European market, in particular the Czech Republic. The main export products are anti-virus software, business automation systems, accounting software, as well as outsourced technical support services, etc. [2]. From an economic point of view, trade in information services between Ukraine and the Czech Republic demonstrates stable growth and high potential benefits for both countries [3]. However, a comparison of the main economic indicators of Ukraine and the Czech Republic shows different levels of economic development, trade activity and investment attractiveness [4]. The volume of exports of information services to the Czech Republic showed an increase from 2019 to 2021 - from UAH 235 thousand to UAH 264 thousand, which indicates a growing demand for information services of the enterprise in the Czech Republic [1]. When exploring ways to improve the company's export activities, a two-stage approach was chosen and justified [5]. The first element is to improve the existing organisational structure, namely to reduce the number of employees in the printing department to one person and to transfer the department to the deputy director for financial affairs due to the department's unprofitability, since the creation of a separate department for international economic activity entails additional costs, it is necessary to improve the qualifications of existing employees of the economic department through additional training. This step will ensure better communication between the company and its foreign partners. The second element for successful integration into the Czech market is that the company needs to adapt its products and services to meet the requirements of local consumers, standards and legislation. This will help to create a competitive offer that meets the cultural, linguistic and technical characteristics of the market. The results of this analysis can be directly applied in the practice of Ukrainian and foreign enterprises to develop foreign economic relations between Ukraine and the countries of Eastern Europe, the Czech Republic in particular.
Research and development of information services export by domestic companies to the countries of Eastern Europe
Keywords: 8.292.00.01; експорт; інформаційні послуги; удосконалення; міжнародна економічна діяльність; прогнозування; export; information services; improvement; international economic activity; forecasting. List of used literature sources. Kaskevych; V. (2024). Export of Services in the Field of Information Technology: Opportunities and Challenges. Available at: https://nzlubp.org.ua/index.php/journal/article/view/1220. Urban Information Systems; 2024. About the Company. Available at: http://www.ukrbook.net/vydav_dil.html. Naydenko; Ya. O. (2020). Development of Ukraine’s Economic Relations with the Czech Republic. Available at: http://dspace.wunu.edu.ua/bitstream/316497/41510/1. Embassy of Ukraine in the Czech Republic (2024). Trade and Economic Cooperation Between Ukraine and the Czech Republic. Available at: https://czechia.mfa.gov.ua/spivrobitnictvo/358-torgovelyno-jekonomichne-spivrobitnictvo-mizh-ukrajinoju-ta-chehijeju. Babiy; I. (2016). The Impact of Factors on Ensuring the Foreign Economic Activity of Industrial Enterprises. Available at: http://dspace.wunu.edu.ua/bitstream/316497/22559